SEDIMENTS IN THE TERTIARY TANKHOI FIELD, SOUTH BAIKAL BASIN: STRATIGRAPHY, CORRELATION AND STRUCTURAL TRANSFORMATIONS IN THE BAIKAL REGION - S. V. Rasskazov; N. A. Lyamina; I. V. Luzina; G. P. Chernyaeva; I. S. Chuvashova; M. V. Usoltseva (Геодинамика и тектонофизика, 2015)
Biostratigraphic and lithofacial studies of sediments in the Tankhoi Tertiary field, which evolution reflects transformations of the terrain in the Baikal region at the Oligocene-Miocene, Early-Middle Miocene, Miocene-Pliocene and Early-Late Pliocene transitions. The main part of the field is composed of clastic molassoids formed during 'early orogen' stage in the coastal part of an extensive paleobasin with a slow water current and in shallow lakes of the Mishikha-Klyuevka and Osinovka river paleobasins that formed, respectively, at the Oligocene-Miocene and Early-Middle Miocene boundaries. In the Miocene, as suggested by analyses of malacofauna and diatoms, South Baikal was a major, quite deep paleolake. These water bodies were related in the Miocene as evidenced by the partial similarity of diatom species found in South Baikal and the Tunka valley, as well as the presence of similar endemic fauna species in the sediments. Accumulated coarse, mainly proluvial-alluvial deposits are indicators of the tectonic activity that resulted in a dramatic ‘late orogen’ increase of contrasting features of the regional terrain.